StatesCare-The cure for patient healthcare - Deane Waldman (Archives of Community Medicine and Public Health - Peertechz Publications, 2019)
Clinical physicians believe they are drowning . . . because they are! Between complying with an ever-changing landscapeof time-wasting federal regulations, avoiding Health Insurance Portability and Accountability Act violations, plus the entire billing process, who can keep up with the literature, study a patient's medical history, or even talk with a patient? Yet, here I am adding another task to a plate already overfl owing. Doctors are turning their backs on the sickest patient of all, named U.S. Healthcare System. The current attending physicians-Congress-have been treating this patient for more than fi fty years. More accurately, they have been poisoning the patient for half a century.